A follow-up study on fertility and menstrual pattern in infertile patients after laparoscopy in a tertiary care hospital in Bangladesh (BIRDEM Medical Journal, 2020)
Background: Routine use of diagnostic laparoscopy for the evaluation of all cases of female infertility is under debate. Until now, laparoscopy has been widely used as a diagnostic and therapeutic means of treating infertility. This study investigates the fertility outcome for women 2 to 3 years after laparoscopic management. It assessed the benefit and effectiveness of both diagnostic and laparoscopic ovarian drilling regarding reproductive outcome and menstrual regularity.Methods: From May 2013 to November 2014, a total of 303 infertile women undergoing laparoscopy at BIRDEM Hospital, were asked to participate in the study. Sixty subjects were lost to follow up making the study sample size 243.Results: Mean age at the time of laparoscopy was 29.86 ± 4.6 (range 21 - 43) years, 61.7% of women (150 cases) were nulliparous, 38.3% (93 cases) had one child, abortion or ectopic pregnancy. From the time of index surgery to follow-up, 40.3% (98) of women who had tried to conceive had home pregnancy test positive and 25.5% (62) had a live birth following their surgery. Among these 62 subjects, 33 underwent Laparoscopic Ovarian Drilling (LOD) and other 29 had diagnostic laparoscopy along with or without other laparoscopic manipulations. A Chi-square test has revealed that there was significant increase in regularization of menstrual cycle among irregularly menstruating women after laparoscopy indicating regular ovulatory cycles.Conclusion: Laparoscopic procedures can lead to positive results while treating infertility as well as menstrual disturbances, thus establishing a defined position in current fertility practice.Birdem Med J 2020; 10(2): 125-129